PERLINDUNGAN HUKUM TERHADAP PASIEN KORBAN MALPRAKTEK MEDIS DALAM PERSPEKTIF HUKUM PERDATA - Siti Maryam (Universitas Islam Malang, 2021)
This study aims to determine the responsibility of health services or hospitals to patients who are victims of medical malpractice, legal protection for patients as consumers of services in the field of medical services, and legal protection for patients as consumers of services in the field of medical services. The type of research used in this paper is normative legal research or library research. The approach method used in this research is the statutory approach. Secondary research sources used include primary legal materials and tertiary legal materials. Based on the results of the study, it can be concluded that 1) The form of regulation of medical personnel who commit malpractice is regulated in Article 19 paragraph (1) of Law no. 8 of 1999 concerning Consumer Protection and in Article 58 paragraph (1) of Law no. 36 of 2009 concerning Health which discusses compensation for a person, health worker and or health provider who causes losses due to errors or omissions in health services; 2) The form of deviation from the agreement between a doctor and a patient that can harm the patient is a breach of contract or an unlawful act committed by a doctor. The losses suffered by the patient can be in the form of material or immaterial losses; and 3) Civil liability for medical personnel must be from unlawful acts (onrechtmatige daad) in accordance with the provisions of Article 1365 of the Civil Code and the responsibility of hospitals related to vicarious liability under the provisions of Article 1367 of the Civil Code.Keywords: patient losses, patient protection, responsibility of medical personnel/officers (doctors) and health service providers, malpractice Penelitian ini bertujuan untuk mengetahui tanggungjawab layanan Kesehatan atau RS terhadap pasien korban malpraktek medis, perlindungan hukum bagi pasien sebagai konsumen jasa di bidang pelayanan medis, dan perlindungan hukum bagi pasien sebagai konsumen jasa di bidang pelayanan medis. Jenis penelitian yang digunakan dalam penulisan ini adalah penelitian hukum normatif atau hukum kepustakaan (library research). Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan perundang-undangan. Sumber penelitian sekunder yang digunakan meliputi bahan hukum primer dan bahan hukum tersier. Berdasarkan hasil penelitian dapat ditarik kesimpulan bahwa 1) Bentuk pengaturan terhadap tenaga medis yang melakukan malapraktik diatur dalam Pasal 19 ayat (1) Undang – Undang No. 8 Tahun 1999 tentang Perlindungan Konsumen dan dalam Pasal 58 ayat (1) Undang – Undang No. 36 tahun 2009 tentang Kesehatan yang membahas ganti rugi terhadap seseorang, tenaga kesehatan dan atau penyelenggara kesehatan yang menimbulkan kerugian akibat kesalahan atau kelalaian dalam pelayanan kesehatan; 2) Bentuk bentuk penyimpangan perjanjian antara dokter dengan pasien yang dapat merugikan pasien adalah wanprestasi atau perbuatan melawan hukum yang dilakukan oleh dokter. Kerugian yang diderita pasien dapat berupa kerugian materiil maupun inmateriil; dan 3) Pertanggung jawaban perdata terhadap tenaga medis yaitu harus dari perbuatan yang melawan hukum (onrechtmatige daad) sesuai dengan ketentuan Pasal 1365 KUHPerdata dan tanggung jawab RS terkait vicarious liability ketentuan pasal 1367 KUHPerdata.Kata Kunci : kerugian pasien, perlindungan pasien, tanggungjawab tenaga/petugas medis (dokter) dan penyedia layanan Kesehatan